How to Measure Sedentary Behavior at Work? - Boudet, Gil; Chausse, Pierre; Thivel, David; Rousset, Sylvie; Mermillod, Martial; Baker, Julien S.; Parreira, Lenise M.; Esquirol, Yolande; Duclos, Martine; Dutheil, Frédéric (Frontiers in Public Health, 2019)
Prolonged sedentary behavior (SB) is associated with increased risk for chronic conditions, and due to technological advances, the working population is located in an office setting with high occupational exposure to SB. There is a new focus in assessing, understanding and reducing SB in the work setting. So, measuring accurately SB at work is a new goal. There are many subjective (questionnaires) and objective methods (monitoring with wearable devices) available to determine SB. Therefore, we aim to provide a global understanding on methods currently used for SB assessment at work. Available questionnaires are the most accessible method for large population studies with a limited budget. SB at work (time sitting) is accessible from some specific measuring devices and it is therefore possible to quantify SB in measuring PA at work. For restrictive groups, SB at work can be objectively measured with wearable devices (accelerometers, heart-rate monitors, pressure meters, goniometers, electromyography meters, gas-meters) and the results can be associated and compared with a subjective measure (questionnaire). The number of devices worn can increase the accuracy but make the analysis more complex and time consuming.